Weakly Nonlinear and Nonlinear Magneto-convection under Thermal Modulation - Kiran, Palle; Bhadauria, B.S.; Narasimhulu, Y. (Journal of Applied Nonlinear Dynamics, 2026)
Both oscillatory and chaotic convection are studied using weakly non- linear and nonlinear theories. A weakly nonlinear analysis was em- ployed to derive Complex Ginzburg-Landau amplitude equation. The time dependent temperatures of the plates are considered in three ways, out of phase, lower plate and in phase modulation. The first two temperature profiles show impact on heat and mass transfer and the dynamics of the problem. It is also found that in-phase tempera- ture modulation has negligible effect; while out of phase modulation and only lower plate modulation have significant effects on heat and mass transport. Heat mass transfer is measured in the system in terms of the Nusselt and Sherwood numbers. Heat mass transfer be- comes rapid on either increasing Rs,Pr, λ, δ or decreasing Q, Γ, ε, Ω. Further, the Lorentz model has been simplified under modulation ef- fect, and it is observed that, the chaotic nature of the system may altered with modulation. Unstable solution for OPM, stable solu- tions for IPM, LBMO is found depending on the suitable values of modulation parameters.